Meningkatkan Literasi dan Kreativitas Siswa Melalui Majalah Dinding (MADING) di SDN 06 Sungai Kayu Ara Kabupaten Siak - Sakur, Sakur; Julita, Sari; Simbolon, Parsiholan; Azmi, Muhammad Fiqri; Nabila, Rahma; Zulhendri, Zulhendri (EL-EMIR INSTITUTE, 2025)
This research aims to increase student literacy and creativity at SD Negeri 06 Sungai Kayu Ara through the activity of making wall magazines (mading) with the theme